2013
DOI: 10.3390/molecules18089293
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Oxidant and Anti-Inflammatory Activities of Inonotus obliquus and Germinated Brown Rice Extracts

Abstract: Abstract:Inonotus obliquus (IO) is parasitic mushroom that grows on birch and other trees in Russia, Korea, Europe and United States. However, IO is not readily available for consumption due to its high cost and difficult growth. In this regard, IO was inoculated on germinated brown rice (GBR) in the present study and the antioxidant and anti-inflammatory activities of the IO grown on germinated brown rice (IOGBR) extracts were evaluated extensively and compared with those for IO and GBR. IOGBR showed highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 28 publications
1
25
0
1
Order By: Relevance
“…LPS-induced Toll-like receptor-4 dimerization dramatically increases the levels of oxidative stress-related molecules as NO and PGE2, and it results in pro-inflammatory responses [33]. Correspondingly, specific inhibition of the production of these molecules is a general way to suppress intracellular pro-inflammatory signals [34].…”
Section: Discussionmentioning
confidence: 98%
“…LPS-induced Toll-like receptor-4 dimerization dramatically increases the levels of oxidative stress-related molecules as NO and PGE2, and it results in pro-inflammatory responses [33]. Correspondingly, specific inhibition of the production of these molecules is a general way to suppress intracellular pro-inflammatory signals [34].…”
Section: Discussionmentioning
confidence: 98%
“…The treatment of STZ‐induced diabetic Wistar rats with polysaccharide extracts of I. obliquus for 6 weeks decreased IL‐1β levels, retarded TNF‐α production, and lowered the formation of ROS (Diao et al, ). Similarly, the treatment of H 2 O 2 ‐stimulated mice livers with extracts obtained from I. obliquus grown on germinated brown rice ( IOGBR ) enhanced both antioxidant enzymes activity and reduced malondialdehyde (MDA) levels (Debnath, Park, Kim, Jo, & Lim, ). These authors also reported that IOGBR extracts exhibited antiinflammatory effects in a lipopolysaccharide‐stimulated RAW 264.7 cell line by suppressing proinflammatory mediators such as NO, PGE2, iNOS, COX‐2, TNF‐α, IL‐1β, and IL‐6 (Debnath et al, ).…”
Section: Influence Of I Obliquus Extract On the Immune Systemmentioning
confidence: 99%
“…Similarly, the treatment of H 2 O 2 ‐stimulated mice livers with extracts obtained from I. obliquus grown on germinated brown rice ( IOGBR ) enhanced both antioxidant enzymes activity and reduced malondialdehyde (MDA) levels (Debnath, Park, Kim, Jo, & Lim, ). These authors also reported that IOGBR extracts exhibited antiinflammatory effects in a lipopolysaccharide‐stimulated RAW 264.7 cell line by suppressing proinflammatory mediators such as NO, PGE2, iNOS, COX‐2, TNF‐α, IL‐1β, and IL‐6 (Debnath et al, ). Ethanolic extract (70%) of I. obliquus retarded the phosphorylation of Akt, 1kBα, and MAPKs in lipopolysaccharide‐activated macrophages in a dose‐dependent manner (Kim et al, ).…”
Section: Influence Of I Obliquus Extract On the Immune Systemmentioning
confidence: 99%
“…When they were exposed to H 2 O 2 , BMSCs were injured and maybe release the proinflammatory cytokines, which in turn damage the BMSCs and induce the apoptosis of BMSCs. IL-6 and TNF-α, potent proinflammatory cytokines, play a critical role in initiating and sustaining the inflammatory response [19]. Meantime, IL-6 and TNF-α are also pro-apoptotic cytokines because they promote neuronal apoptosis induced by hypoxia-ischemia [20].…”
Section: Discussionmentioning
confidence: 99%